2014
DOI: 10.5953/jmjh.2014.21.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Concept Analysis of Self-help Groups

Abstract: The purpose of the study was to identify the attributes of self-help groups, their antecedents and consequences relating to self-help groups. Methods: We used the Walker and Avant (2010) method using the key word "self-help groups" the Korea Education and Research Information Service (www.riss4u.net), Pubmed, CINAHL and ProQuest for articles on this topic published between January 2000 and March 2013 were searched. Ultimately, 64 domestic and 21 foreign papers were selected for in-depth analysis. Results: The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…"Sorrow about the stigma of being a patient" was also newly identified in the fieldwork phase. Social stigma causes individuals to have negative emotions such as anxiety, including stress, which leads to the formation of a negative self-concept and destruction of self-integration [56]. A study by Songtag [57] reported that patients feared social discrimination, and suffering from stereotyping is a bigger problem than physical suffering for patients who have experienced an illness.…”
Section: Discussionmentioning
confidence: 99%
“…"Sorrow about the stigma of being a patient" was also newly identified in the fieldwork phase. Social stigma causes individuals to have negative emotions such as anxiety, including stress, which leads to the formation of a negative self-concept and destruction of self-integration [56]. A study by Songtag [57] reported that patients feared social discrimination, and suffering from stereotyping is a bigger problem than physical suffering for patients who have experienced an illness.…”
Section: Discussionmentioning
confidence: 99%